Father’s involvement and parenting styles in Portuguese families. The role of education and working hours - Monteiro, Lígia (2018)
Early studies on fathers focused mainly on his presence in or absence from children’s lives, and the amount of time they spent with them. More recently, several authors have stated the importance of understanding the quality of father involvement to comprehend fully its impact on child development. However, studies have also reported that socio-demographic variables, namely, father educational levels and employment status affect parenting and children outcomes. The aims of this study were to analyze a sample of 465 Portuguese two-parent families with pre-school age children, looking for associations between father involvement in care/socialization activities and paternal parenting styles while testing for the moderating effect of father educational levels and working hours. Fathers reported on their own parenting styles and mothers described the father’s involvement. Fathers’ working hours moderated the relation between his authoritative parenting style and involvement in teaching/discipline and play activities. In addition, fathers’ education moderated the relation between his authoritative style and involvement in direct care and teaching/discipline. Given the different roles that fathers can assume in their children’s lives, it is important to understand the mechanisms of paternal participation, and identify the factors which explain the differences in effective care so that we can promote higher positive involvement.